Impact and mechanism of the “three rights separation” of agricultural land on the output efficiency of arable land in China：Based on the production factor perspective - GONG Maogang, CHEN Sifan (Ziyuan Kexue, 2024)
[Objective] Improving the output efficiency of arable land is the core focus of ensuring national food security. The reform of “three rights separation” of agricultural land has significantly increased the enthusiasm of farmers for land management through empowerment, which inevitably has a significant impact on the output efficiency of arable land. The degree of influence and mechanisms involved deserve further investigation. [Methods] Based on the panel data from 146 prefecture-level cities in China from 2013 to 2021, this study first calculated the output efficiency of arable land using the data envelopment analysis (DEA)-Malmquist index method. It then employed a multi-period difference-in-differences test to examine the impact of the “three rights separation” of agricultural land on the output efficiency of arable land. Finally, by constructing a panel fixed effects model with interaction terms, it explored the mechanisms through which the “three rights separation” of agricultural land affects the output efficiency of arable land. [Results] The reform of the “three rights separation” of agricultural, significantly promoted the improvement of the output efficiency of arable land in China. This effect is also reinforced by legal clarity, and the results remains robust after conducting robustness tests such as placebo tests. Heterogeneity analysis revealed that the positive impact of the “three rights separation” of agricultural land on the output efficiency of arable land is more significant in the western region, northeastern region, groups with high per unit sown area planting industry output value, and groups with fiscal support for agriculture below the median level. Mechanism analysis found that the “three rights separation” of agricultural land mainly affects the output efficiency of arable land by weakening the impact of large-scale land management on the output efficiency of arable land and enhancing the impact of rural labor transfer on the output efficiency of arable land. [Conclusion] In the future, China should continue to deepen rural land system reform along the current path, further unleash the policy dividends of the “three rights separation” of agricultural land, and improve the efficiency of arable land resource utilization.